Ultrathin Reduced Graphene Oxide Films as Transparent Top‐Contacts for Light Switchable Solid‐State Molecular Junctions. (14th June 2013) - Li, Tao; Jevric, Martyn; Hauptmann, Jonas R.; Hviid, Rune; Wei, Zhongming; Wang, Rui; Reeler, Nini E. A.; Thyrhaug, Erling; Petersen, Søren; Meyer, Jakob A. S.; Bovet, Nicolas; Vosch, Tom; et al.
<x xml:space="preserve">Abstract</x> A new type of solid‐state molecular junction is introduced, which employs reduced graphene oxide as a transparent top contact that permits a self‐assembled molecular monolayer to be photoswitched in situ, while simultaneously enabling charge‐transport measurements across the molecules. The electrical switching behavior of a less‐studied molecular switch, dihydroazulene/vinylheptafulvene, is described, which is used as a test case. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>